(untitled) (Research, Society and Development, 2021)
With the advent of the Water Law, public entities began to have a more comprehensive look at water resources. Water management began to reconcile with environmental issues. This study was carried out with the aim of analyzing the legal advances resulting from actions to democratize access to water in a region with a water deficit, such as the semiarid region. To carry out this study, the methodology of deductive and investigative research was used, with a bibliographic, exploratory and descriptive nature. Although Brazilian society in its various sectors is integrated in the planning of actions aimed at the sustainability and democratization of natural resources, putting national legislation into practice, it is essential that massive and intense awareness occurs for the Brazilian population to claim its representatives the elaboration of laws that assist in the execution of public policies that ensure an improvement in the quality of life and an ecologically balanced and sustainable space.